(untitled) (Atlanti, 2016)
In the paper the author is addressing the issue of data protection by observing several points of the view. With the overview of diverse legislation in Europe and of definitions of personal data through different legal acts, the author is giving several starting points toward many questions, which arise on data protection issue. One of the most important points is protecting human rights and redressing the injustices. Next question, which arises, is the issue of data protection related to the same data in different archival records, in different archives and in different countries. The issue is discussed on the overview of the archival records of courts and military courts in the context of protecting human rights as well as on the archival records of former Yugoslavia.